Is Exclusive Small Airway Asthma a Possibility? - Russell J. Hopp (Allergies)
Although the small airway component of chronic asthma is becoming a more important topic, its impact in the daily assessment of pediatric asthma is limited. The intrinsic airway autonomic control in asthma suggests some potential mechanisms by which more distal obstruction may dominate in some situations. We suggest theoretical possibilities for small airway dominance and present clinical data supporting this possibility.